Acceptability of self‐taken vaginal HPV sample for cervical screening among an under‐screened Indigenous population. (7th January 2019) - Adcock, Anna; Cram, Fiona; Lawton, Beverley; Geller, Stacie; Hibma, Merilyn; Sykes, Peter; MacDonald, E Jane; Dallas‐Katoa, Wendy; Rendle, Bronwyn; Cornell, Tracey; Mataki, Tania; Rangiwhetu, Tania; et al.
Abstract : Background: Human papillomavirus (HPV), the causative agent of cervical cancer, can be screened for using self‐collected vaginal samples (self‐testing). This may overcome barriers to screening for Māori women who suffer a greater burden of cervical disease than New Zealand European women. Aims: This study aimed to explore the potential acceptability of HPV self‐testing for never/under‐screened (self‐reported no cervical screen in 4+ years, aged 25+) Māori women by Kaupapa Māori (by, with and for Māori) mixed methods, involving hui (focus groups/interviews) and survey. Materials and Methods: Community‐based researchers ran hui with women in four regions ( N = 106) and supported hui participants to collect survey data ( N = 397). Healthcare providers (HCPs) were also interviewed ( N = 17). Hui data were thematically analysed. Survey data were analysed by age group, rural/urban, primary health organisation (PHO) enrolment, and time since last cervical screen. Results: Most survey participants were PHO‐enrolled (87.15%) and attended regularly (71.79%), but did not attend regular cervical screening. A desire for bodily autonomy, including whakamā (embarrassment/shyness/reticence), was the most frequently cited barrier. Three in four women reported being likely/very likely to do an HPV self‐test. Nine in ten women reported being likely/very likely to attend follow up if they receive a positive HPV test result. Women and HCPs in the hui emphasised the importance of health literacy, cultural competence and empathetic support. Conclusion: The findings indicate that with a culturally competent introduction of HPV self‐testing, many currently never/under‐screened Māori women would be willing to be screened and followed up if necessary. HPV self‐testing has the potential to save lives.